2017
DOI: 10.1111/ijpo.12227
|View full text |Cite
|
Sign up to set email alerts
|

Associations between birthweight and overweight and obesity in school‐age children

Abstract: High birthweight term and LGA preterm children had increased adjusted odds of obesity in school-age compared to their NBW counterparts. Physicians may provide counselling early in life for families of large infants to help prevent future obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
2
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 32 publications
(49 reference statements)
7
48
2
7
Order By: Relevance
“…Women with overweight or obesity are more likely to give birth to high birth weight infants . Infants with a high birth weight tend to become children with overweight or obesity . Pregnant women with overweight or obesity are also more likely to require a Caesarean section, partly because of their increased risk of giving a birth to high birth weight infants.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Women with overweight or obesity are more likely to give birth to high birth weight infants . Infants with a high birth weight tend to become children with overweight or obesity . Pregnant women with overweight or obesity are also more likely to require a Caesarean section, partly because of their increased risk of giving a birth to high birth weight infants.…”
Section: Discussionsupporting
confidence: 59%
“…69 Infants with a high birth weight tend to become children with overweight or obesity. 70 Pregnant women with overweight or obesity are also more likely to require a Caesarean section, 61 partly because of their increased risk of giving a birth to high birth weight infants. Almost all the aforementioned maternal overweight-and obesity-related adverse outcomes have also been positively linked with an increased risk of childhood-onset T1DM ( Table 1 and Figure 2A).…”
Section: Maternal Overweight and Obesitymentioning
confidence: 99%
“…Because of this, we used 3 months rather than birth as Pathways to obesity from infancy to childhood | 625 a baseline. A previous study has noted that birthweight bears little relation to weight at 5 years (23), but another recent study found an association between high birthweight and raised BMI in midchildhood (24). However, it is not clear whether this association reflects increased fat mass, or just tracking of lean mass, because another recent study found that BMI at 9 months was associated only with fat free mass in adulthood (25).…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of childhood obesity following intensive glycemic control during hyperglycemic pregnancies had been theorized by researchers and clinicians based on the continuous relationship between maternal glycemia and birth weight 235,237,316 , and the relationship between higher birth weight and childhood excess weight. 311,317,318 In reviewing the literature, it appeared that only a few studiesthree to be exacttested this hypothesis, each with non-significant results ( Figure 6.2). The lack of significant effect of intensive glycemic management in women with mild GDM on childhood obesity might have been due to a limited normalisation of the intrauterine diabetes exposure.…”
Section: Prenatal Intervention To Limit Intrauterine Exposure To Diabmentioning
confidence: 99%